Financing cross-border road connectivity: Potential impact on Sabah’s output—An input-output table analysis - Rafiq Idris; Azizan Morshidi; Kasim Mansur; Rizal Zamani Idris (EnPress Publisher, LLC, 2024)
Fiscal spending for road construction to link Kalabakan, Sabah, Malaysia with North Kalimantan, Indonesia is an idea that have been proposed for over 20 years. The announcement for the relocation of Indonesia’s capital city from Jakarta to East Kalimantan give a strong justification for the construction of the Serudong-Simanggaris road. The fact that population size is big in Kalimantan and strong purchasing power is estimated in North and East Kaliamantan provide a strong argument for the need to have a road link. Having said that, the effect of road construction on output growth is not clear. The purpose of this study is to estimate the impact of road construction and the business activities across two sectors being assumed on output Sabah’s output growth. Based on the input-output analysis conducted using the output multiplier, the one-off road construction would lead to 1.8% growth in Sabah’s overall output.